Агенції місцевого економічного розвитку як елемент електронної демократії - Жуковська, Юліана; Марковець, Олександр (Видавництво Львівської політехніки, 2017)
The article presents an analytical review of teaching and Internet sources that explain and describe the activities of Regional Economic Development Agencies. Displaying perspective of different authors and based on them formulated the main idea. In addition, more considered one of the most important tasks of the Agency – social projects.
Keywords: агенція; економічний розвиток; громада; проекти; активізація громади; організація